2021
DOI: 10.1111/1742-6723.13873
|View full text |Cite
|
Sign up to set email alerts
|

Unplanned blood use within 24 hours of emergency department presentation: A cohort study in an ageing population

Abstract: Objective This research aims to elucidate drivers of blood use in an older population, with a focus on unplanned transfusions following ED presentation. Methods In a retrospective cohort study we examined 2015 data for ED presentations and blood use in two hospitals serving a population containing a high proportion (21%) of adults aged ≥65 years. Unplanned blood use was defined as any transfusion ≤24 h of presentation. Data were analysed by age, sex, Major Diagnostic Category, triage category and time to trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…9,29 In a secondary analysis of the Pragmatic Randomized Optimal Platelet and Plasma Ratios (PROPPR) trial, McCrum et al found that after anatomic hemostasis, females received lower volumes of all blood products, with a 38% reduction in plasma, 49% reduction in platelets, and 49% reduction in red blood cell volumes. 30 Males ultimately receive relatively more transfusions, 31 which translates into higher rates of transfusionrelated complications, such as ventilator-associated pneumonia, organ failure, acute respiratory distress syndrome, and longer intensive care unit and hospital length of stay. [32][33][34] These sex-specific differences are even more pronounced when stratifying females by hormonally active ages.…”
Section: Mechanisms Underlying Female-specific Hypercoagulability And...mentioning
confidence: 99%
“…9,29 In a secondary analysis of the Pragmatic Randomized Optimal Platelet and Plasma Ratios (PROPPR) trial, McCrum et al found that after anatomic hemostasis, females received lower volumes of all blood products, with a 38% reduction in plasma, 49% reduction in platelets, and 49% reduction in red blood cell volumes. 30 Males ultimately receive relatively more transfusions, 31 which translates into higher rates of transfusionrelated complications, such as ventilator-associated pneumonia, organ failure, acute respiratory distress syndrome, and longer intensive care unit and hospital length of stay. [32][33][34] These sex-specific differences are even more pronounced when stratifying females by hormonally active ages.…”
Section: Mechanisms Underlying Female-specific Hypercoagulability And...mentioning
confidence: 99%